THE POWER OF CONNECTION: HOW COMBINING TEACHING METHODS AND STUDENT PSYCHOLOGY BOOSTS ENGAGEMENT - Abdusattorova Ra’no Jakhangirovna; Djumaniyazova Zilola Navfal qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
Nowadays higher education focuses on digital tools, but technology cannot replace "human connection." Therefore, this paper explores integrating pedagogy and student psychology to improve learning. Specifically, it examines how Educational Escape and Lesson Study reduce anxiety and help students reach the "Flow State." By prioritizing emotional well-being, these methods naturally boost engagement. In conclusion, the future of education lies in the link between teaching techniques and the learner’s psychological needs.